A review of electrical and piezoelectric properties of nanocellulose biocomposites - Habib, Abdul; Salit, Mohd Sapuan; Zainudin, Edi Syams; Afdzaluddin, Atiqah (Walter de Gruyter, 2024)
The increasing request for lightweight, environmentally sustainable materials with versatile functionality and strong mechanical properties is driving renewed interest in nanocellulose for electrical applications. Nanocellulose, a biologically derived polymeric nanomaterial, has seen significant growth in the global market due to advancements in nanotechnology and the increasing need for sustainable materials. This has accelerated research into the development of cellulose-based nanomaterials. However, nanocellulose on its own does not inherently possess the ability to function as a conductive material. To address this limitation, researchers have explored various modifications, such as combining nanocellulose with conductive materials or applying specific chemical treatments. These approaches have been shown to enhance the electrical conductivity of nanocellulose, making it suitable for use in electrically conductive composites. Over the past few decades, nanocellulose composites have been extensively studied for their applications in energy, electronics, biomedicine, health, and environmental sectors. Nanocellulose possesses a unique combination of exceptional properties, including biodegradability, renewability, and a distinctive fibrous structure, proving that it is the best choice for these uses. The superior electrical properties of nanocellulosebased composites, coupled with their flexibility, ease of production, and biocompatibility, make them highly desirable for various advanced technological applications. Significant advancements have been achieved by researchers in fabricating various types of nanocellulose materials and exploring their potential in nanogenerators, humidity sensors, gas sensors, and supercapacitors. The ability to modify the surface of nanocellulose and its robust properties offer numerous opportunities for creating hybrid materials within the electrical domain.